Percutaneous external fixator pins with bactericidal micron-thin sol–gel films for the prevention of pin tract infection. (September 2015) - Qu, Haibo; Knabe, Christine; Radin, Shula; Garino, Jonathan; Ducheyne, Paul
Abstract: Risk of infection is considerable in open fractures, especially when fracture fixation devices are used to stabilize the fractured bones. Overall deep infection rates of 16.2% have been reported. The infection rate is even greater, up to 32.2%, with external fixation of femoral fractures. The use of percutaneous implants for certain clinical applications, such as percutaneous implants for external fracture fixation, still represents a challenge today. Currently, bone infections are very difficult to treat. Very potent antibiotics are needed, which creates the risk of irreversible damage to other organs, when the antibiotics are administered systemically. As such, controlled, local release is being pursued, but no such treatments are in clinical use. Herein, the use of bactericidal micron-thin sol–gel films on metallic fracture fixation pins is reported. The data demonstrates that triclosan (2, 4, 4′-trichloro-2′-hydroxydiphenylether), an antimicrobial agent, can be successfully incorporated into micron-thin sol–gel films deposited on percutaneous pins. The sol–gel films continuously release triclosan in vitro for durations exceeding 8 weeks (longest measured time point). The bactericidal effect of the micron-thin sol–gel films follows from both in vitro and in vivo studies. Inserting percutaneous pins in distal rabbit tibiae, there were no signs of infection around implants coated with a micron-thin sol–gel/triclosan film. Healing had progressed normally, bone tissue growth was normal and there was no epithelial downgrowth. This result was in contrast with the results in rabbits that received control, uncoated percutaneous pins, in which abundant signs of infection and epithelial downgrowth were observed. Thus, well-adherent, micron-thin sol–gel films laden with a bactericidal molecule successfully prevented pin tract infection.